2020
DOI: 10.31744/einstein_journal/2020ao5225
|View full text |Cite
|
Sign up to set email alerts
|

Long-latency auditory evoked potential in children with stuttering

Abstract: Analisar os valores de latência e amplitude do Mismatch Negativity e potencial cognitivo P300 em crianças com gagueira, sem queixas auditivas, com limiares auditivos dentro dos padrões de normalidade, comparando aos achados de um Grupo Controle. Métodos: Estudo transversal, do qual participaram 50 crianças de ambos os sexos, sendo 15 com gagueira e 35 sem gagueira, entre 6 e 11 anos de idade, sem diagnóstico de patologias otológicas ou outras doenças. Todas as crianças realizaram avaliação audiológica periféri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 23 publications
0
5
0
Order By: Relevance
“…No studies were found describing the morphology of MMN waves in patients with ASD, although there is a consensus in the literature that abnormalities in this parameter indicate atypical neural synchrony, which enables us to infer that individuals with ASD may present it, and, in the sample of the present study, there were abnormalities in 47,06% of the patients. 48,58,59 Even though the analysis of wave morphology has shown abnormalities in some patients in the SG, there was no statistically significant correlation with the results of wave latency and amplitude, which also demonstrates a heterogeneity and variability in ASD characteristics, with individual differences in MMN response in this population.…”
Section: Discussionmentioning
confidence: 79%
See 1 more Smart Citation
“…No studies were found describing the morphology of MMN waves in patients with ASD, although there is a consensus in the literature that abnormalities in this parameter indicate atypical neural synchrony, which enables us to infer that individuals with ASD may present it, and, in the sample of the present study, there were abnormalities in 47,06% of the patients. 48,58,59 Even though the analysis of wave morphology has shown abnormalities in some patients in the SG, there was no statistically significant correlation with the results of wave latency and amplitude, which also demonstrates a heterogeneity and variability in ASD characteristics, with individual differences in MMN response in this population.…”
Section: Discussionmentioning
confidence: 79%
“…No studies were found describing the morphology of MMN waves in patients with ASD, although there is a consensus in the literature that abnormalities in this parameter indicate atypical neural synchrony, which enables us to infer that individuals with ASD may present it, and, in the sample of the present study, there were abnormalities in 47,06% of the patients. 48 58 59…”
Section: Discussionmentioning
confidence: 99%
“…Blood oxygen level dependent tests of auditory function show differences in functional lateralisation between stutter and non-stutter groups ( Sato et al, 2011 ; Halag-Milo et al, 2016 ). Electroencephalography and magnetoencephalography show differences between stutter and non-stutter groups in auditory oddball (P300; Morgan et al, 1997 ; Kaganovich et al, 2010 ; Jerônimo et al, 2020 ); auditory sensory gating (P1/P50m; Kikuchi et al, 2011 ); mismatch negativity ( Corbera et al, 2005 ; Jansson-Verkasalo et al, 2014 ; Jerônimo et al, 2020 ); and alterations to timing and/or amplitude of the N1/M100 during listening tasks ( Ismail et al, 2017 ; Kikuchi et al, 2017 ) and speech tasks ( Salmelin et al, 1998 ; Beal et al, 2010 , 2011 ; Liotti et al, 2010 ). Conflicting results are sometimes reported (e.g., Blood and Blood, 1984 ; Anderson et al, 1988 ; Khedr et al, 2000 ; Hampton and Weber-Fox, 2008 ; Özcan et al, 2009 ).…”
Section: Discussionmentioning
confidence: 99%
“…This reflected a disorder at the level of the cortex regarding temporal processing related to temporal resolution. Temporal resolution disorders can result in serious abnormality in the detection of rapid changes in speech, resulting in speech and reading impairments particularly in children [21] . As a result of disability in identification of rhythm, stress, and intonation, individual with temporal patterning deficits can suffer from inability to understand and use prosody of speech.…”
Section: Discussionmentioning
confidence: 99%